P81 SIMULTANEOUS TRANS–APICAL AORTIC AND MITRAL VALVE IMPLANTATION IN A PATIENT WITH A DEGENERATED MITRAL BIOPROSTHESIS AND SEVERE AORTIC STENOSIS. (18th May 2022) - D'Ascoli, R; Manzan, E; Prestipino, F; Innelli, P; Cristiano, A; Costantino, M; Stabile, E; Luzi, G
Abstract: Transcatheter Valve–in–Valve implantation has shown promising results in high–risk patients suffering from structural valve deterioration (SVD) of a previously implanted heart valve bioprosthesis. This is a case of a 82–year–old man, with history of multiple previous mitral valve replacement, admitted to the hospital for heart failure. During diagnostic work out he was diagnosed with a severe aortic stenosis and structural degeneration of a mitral valve bioprostheses Epic 29mm, St Jude Medical, (Inc, St Paul, Minn, USA). The heart team defined the patient at high surgical risk profile and was therefore scheduled for a simultaneous mitral and aortic transcatheter valve implantation. Through a double trans–apical approach (Figure A and B), the patient underwent two balloon expandable valves (Sapien 3, Edwards Lifesciences, Irvine, CA, USA) deployment in native aortic (Figure C) and mitral bioprosthesis (Figure D), respectively. Final angiography showed lack of aortic (Figure E) and left atrial (Figure E) regurgitation. The procedure was uneventful as well as the following hospital stay. Post–procedural transesophageal echocardiography confirmed the absence of paravalvular leakage nor aortic or mitral regurgitation. The patient was discharged at home on day 7. Simultaneous transapical transcatheter aortic and mitral valve replacement is technically feasible with the current available technology and can be a possible alternative in patients with high surgical risk.